Effect of ethylene oxide unit number in bis-EMA on the physical properties of additive-manufactured occlusal splint material - Wada, Junichiro; Heponiemi, Paulina; Wada, Kanae; Garoushi, Sufyan; Wakabayashi, Noriyuki; Iwamoto, Tsutomu; Vallittu, Pekka K; Lassila Lippo (Elsevier, 2025)
Purpose: To investigate the effects of the number of ethylene oxide units in bis-EMA on the physical properties of additively manufactured occlusal splints.
Methods: Seven experimental materials containing bis-EMAs with three and 10 ethylene oxide units (BE3 and BE10, respectively) were prepared at different BE10 content rates (BE10-0%, -20%, -30%, -40%, -50%, -60%, and -80%). Half the specimens of each material were aged in boiling water. Flexural strength (FS), flexural modulus (FM), fracture toughness (FT), microwear depth (MD), degree of conversion (DC), water sorption (WSP), water solubility (WSL), color difference between non-aged and aged series (ΔE), and translucency (TP) were evaluated. All the evaluated properties other than FS and MD were analyzed by 1-way ANOVA and Tukey's post hoc analysis, while FS and MD were analyzed by Kruskal-Wallis's test and Bonferroni correction (α=0.05).
Results: BE10-80% revealed the lowest FS (P < 0.01 for BE10-0%, -20%, and -30%) and FM (P < 0.01, for all), while revealing the highest DC, WSP, WSL (P < 0.01 for all) and TP (P < 0.01 for all other than BE10-60%). BE10-50% showed the highest FT (P < 0.01 for all). BE10-50%, -60%, and -80% revealed significantly lower ΔE than others (P < 0.01) and lower MD than BE10-0% (P < 0.05). Regardless of the BE10 content, FS, FM, and FT decreased with aging.
Conclusions: The number of ethylene oxide units affects the physical properties of additively manufactured occlusal splints. The higher number of ethylene oxide units in bis-EMA enhanced the microwear